2011
DOI: 10.1017/s1355617710001633
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Functional Outcome After Out of Hospital Cardiac Arrest

Abstract: The nature of residual cognitive deficits after out of hospital cardiac arrest (OHCA) is incompletely described and has never been defined against a cardiac control (CC) group. The objective of this study is to examine neuropsychological outcomes 3 months after OHCA in patients in a “middle range” of acute severity. Thirty prospective OHCA admissions with coma >1 day and responsive but confused at 1 week, and 30 non-OHCA coronary care admissions were administered standard tests in five cognitive domains. OHCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 21 publications
7
59
1
3
Order By: Relevance
“…Previous diabetes mellitus 41 (12) 59 (18) 19 (11) 25 (15) 16 (11) 23 (16) 17 (14) Bystander defibrillation, n (%) 34 (10) 34 (10) 24 (14) 23 (14) 17 (12) 19 (14 found, and further post hoc analyses showed a statistical significant difference between all patients with cardiac arrest and STEMI control subjects in Italy (Italy: 33°C/STEMI control subjects, P=0.01; 36°C/STEMI control subjects, P=0.003) but no statistical significant difference between the 2 temperature groups (Italy: 33°C/36°C, P=0.59). There were no significant differences found between any of the 3 groups in the other countries (P>0.30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous diabetes mellitus 41 (12) 59 (18) 19 (11) 25 (15) 16 (11) 23 (16) 17 (14) Bystander defibrillation, n (%) 34 (10) 34 (10) 24 (14) 23 (14) 17 (12) 19 (14 found, and further post hoc analyses showed a statistical significant difference between all patients with cardiac arrest and STEMI control subjects in Italy (Italy: 33°C/STEMI control subjects, P=0.01; 36°C/STEMI control subjects, P=0.003) but no statistical significant difference between the 2 temperature groups (Italy: 33°C/36°C, P=0.59). There were no significant differences found between any of the 3 groups in the other countries (P>0.30).…”
Section: Resultsmentioning
confidence: 99%
“…9,10 In a recent review, 30% to 50% of survivors after cardiac arrest were reported to suffer from cognitive impairment. 11 The generalizability of previous studies is poor because of small sample sizes, [12][13][14] missing data, 13,14 and patient selection, that is, the exclusion of those with a poor outcome, 14 inclusion of only patients with severe symptoms, 12 or absence of a nonarrest control group. 11 Optimally, OHCA survivors should be evaluated for the cognitive functions known to be most affected: memory, attention, and executive functions.…”
Section: Clinical Perspective On P 1349mentioning
confidence: 99%
“…A third study illustrated cognitive differences between a control subject group and a patient group following outof-hospital arrest. Two-thirds of the patients showed mild deficits in memory and one-third showed more severe impairments in memory, psychomotor function, and other cognitive domains (Alexander et al, 2011). Newer studies have also explored novel tests that are not as specific and timeconsuming as a complete neurocognitive battery; these have been shown to be more sensitive than the MMSE or the CPC.…”
Section: Cognitive Function In Cardiac Arrest Survivorsmentioning
confidence: 99%
“…In recent practice, the two most common measures of cognitive function for resuscitated cardiac arrest patients have been the cerebral performance category (CPC) score and the mini-mental state examination (MMSE) (Moulaert et al, 2009;Alexander et al, 2011). Both tests provide healthcare providers with rapid yet nongranular diagnostic tools for potentially differentiating a spectrum of cognitive impairments.…”
Section: Introductionmentioning
confidence: 99%
“…1 Owing to the overall decrease in CBF after ischemia, neuronal cell death 1 can occur in major regions of the brain responsible for learning, memory, and cognitive function. 2 It is thought that during global ischemia, PKCd (a novel PKC) levels are elevated causing PKCd to translocate to the nucleus (activation) resulting in cellular damage. In the normal brain, PKCd levels are nominal whereas global ischemia can cause activation/translocation of PKCd.…”
Section: Introductionmentioning
confidence: 99%